Health and access to care: Why it is necessary and urgent to switch from a global public good approach to a commons based approach - Benjamin Coriat; Fabienne Orsi; Jean Francois Alessandrini; Pascale Boulet; Sauman Singh-Phulgenda (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2023)
During the Covid 19 Pandemic, there have been countless calls for the creation of ''global public goods'' or ''global commons'' issued by a variety of actors with sometimes diametrically opposed views, as if the two notions had the same meaning. And indeed, even today these notions are still often used as synonyms and interchangeable, leading to an amalgamation of concepts. The meaning and implications of using one notion or other notion (global public good, global commons) is never examined. We believe that, contrary to the dominant view, it is urgent to put an end to this confusion which is not only of a semantic order and has huge economic and social implications. In this article, we start by recalling what constitutes the notion of ''Global Public Good'' and by extension the content of what can be called the GPG approach (section 1). Then, by difference we present the notion of common good and the commons based approach (section 2). Finally, in a concluding section, we present some of the most significant initiatives taken during the covid-19 pandemic, designed and deployed to producing and distributing health products as common goods (section 3). Our overall ambition being to highlight that the deployment of the commons based approach that we are calling for, is not a utopia, as it is already moving on.
Keywords: F55; H41; I14; K11; O32; 330; International Institutional Arrangements; Public Goods; Health and Inequality; Property Law; Management of Technological Innovation and R&D